Automatic optimization system of peripheral milling process - Vasić, Siniša; Todić, Velimir; Banjac, Dragan (Journal of Production Engineering, 1987)
In the paper the automatic system of internal optimization for peripheral milling process is described. The system is developed and adopted for a personal computer using. The possibility of using this automatic system for external optimization of the peripheral milling process is shorten in the paper as well.